2019
DOI: 10.1039/c8cc10316j
|View full text |Cite
|
Sign up to set email alerts
|

Probing the photovoltaic properties of Ga-doped CdS–Cu2S core–shell heterostructured nanowire devices

Abstract: In this study Ga-doped cadmium sulfide (CdS) nanowires (NWs) were grown through chemical vapor deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Thus, a p-type semiconductor is sought to construct a p–n heterojunction for recombination with n-type CdS to solve the defects of poor charge mobility and a short lifetime. Cu 2 S is a typical p-type semiconductor; its low cost and good light absorption ability have been widely concerned in various research fields. The properties of the photocatalyst are affected by its shape and size. , Especially, Zhang et al reported the synthesis of a snowflake-like Cu 2 S system structure using the template-free method . Because of the high absorbance and surface area of Cu 2 S snowflakes, they exhibit efficient photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a p-type semiconductor is sought to construct a p–n heterojunction for recombination with n-type CdS to solve the defects of poor charge mobility and a short lifetime. Cu 2 S is a typical p-type semiconductor; its low cost and good light absorption ability have been widely concerned in various research fields. The properties of the photocatalyst are affected by its shape and size. , Especially, Zhang et al reported the synthesis of a snowflake-like Cu 2 S system structure using the template-free method . Because of the high absorbance and surface area of Cu 2 S snowflakes, they exhibit efficient photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Taur et al (2012) found the conversion efficiency of the CdS/Cu 2 S solar cell produced by chemical method as η = 0.24 in the annealed sample and η = 0.09 in the non-annealed sample [7]. Lu et al (2019) calculated the short circuit current, open circuit voltage, fill factor and power conversion efficiency of the n-CdS/p-Cu 2 S solar cell produced by the chemical vapor deposition method as 0.152 nA, 0.25 V, 0.445 and 0.405%, respectively [38].…”
Section: Resultsmentioning
confidence: 99%
“…As depicted in Figure 1, for the blank ZnS, the characteristic peaks of ZnS at 28.6 • , 47.6 • and 56.5 • were attributed to the cubic ZnS crystal planes (111), ( 220) and (311) (PDF#65-0309), respectively [23]. For the blank CdS, the CdS characteristic peaks located at 24.8 • , 26.5 • , 28.2 • and 43.7 • were attributed to the crystal planes (100), (002), ( 101) and (110) of hexagonal CdS (PDF#89-2944 CdS), respectively [24]. For CdS@ZnS samples, both the characteristic peaks of CdS and ZnS could be observed [18].…”
Section: Characterization Of Cds@zns Samplesmentioning
confidence: 99%